(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Traumatic rupture of the long head of the biceps (LHB) tendon is increasingly recognized in younger and active individuals. Arthroscopic tenodesis has emerged as a preferred technique over tenotomy due to its ability to preserve muscle contour, restore function, and reduce cosmetic and functional complications. This study investigates the clinical outcomes of arthroscopic suprapectoral biceps tenodesis in traumatic LHB ruptures. Functional scores, strength recovery, and patient satisfaction were assessed. Our results confirm that arthroscopic tenodesis provides superior outcomes compared to historical tenotomy data, supporting its use as a first-line surgical treatment in this population.